EFFECT OF ABATTOIR EFFLUENT ON MACRO INVERTEBRATE ALONG UNGUWA UKU STREAM, GOMBE - MUHAMMAD, KABIRU; PAWKWANDI, LUIS; MOHAMMED UMAR, DANLADI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
The physico-chemical parameters and macroinvertebrates in Anguwa-uku stream Gombe between the months of May through July 2021 within three sampling sites, each 10 m apart were selected along the stretch of the stream and studied to assess the impact of abattoir effluent on macro invertebrate samples. Physico-chemical parameters were within the allowable limits of United States Environmental Protection Agency (USEPA) for fresh water bodies. There were significant differences (p<0.05) in the mean values of Dissolved Oxygen(DO) (2.63) , Total Dissolved Solid TDS(58.00), transparency(68.05), nitrate(0.83) and phosphate(1.50) between the months and through the sampling stations. A total of fifteen genera of benthic macroinvertebrates belonging to five orders (Diptera(29), Decapoda(37), Coleoptera(52), Odonata(3), and Prosobranchia(2 ) were recorded in the three sampling sites of the stream during the study. Pollution tolerant species including Coenagrionidesand Chironomus sp. Dominated the benthic macroinvertebrates with a total number and percentage abundance of 29(43.21%) and 20(31.25%), respectively. Anguwa uku stream is relatively under stress due to dominance of indicators of pollution.